Comparative analysis of low‐altitude ENA emissions in two substorms. Issue 2 (25th February 2013) - Buzulukova, N.; Fok, M.‐C.; Roelof, E.; Redfern, J.; Goldstein, J.; Valek, P.; McComas, D.
Abstract: [1] We report on the dynamics of low‐altitude energetic neutral atom (ENA) emissions during two substorms that occurred during the main phases of two storms: (1) a CIR‐driven storm on 11 October 2008 and (2) a coronal mass ejection (CME)‐driven storm on 5 April 2010. For both of these storms, we have complementary spacecraft and ground‐based observations. The dual‐spacecraft Two Wide‐angle Imaging Neutral‐atom Spectrometers (TWINS) mission obtained ENA images containing low‐altitude emissions (LAEs). Substorm dynamics is inferred from THEMIS all‐sky imagers. TWINS‐observed LAEs are compared with trapped/loss cone proton fluxes from the low‐altitude NOAA/MetOp spacecraft constellation. We find that the timing and intensity profiles of LAEs are different for the two selected events. For the 11 October 2008 event, the LAEs rise during substorm recovery phase and storm main phase. On 5 April 2010, the LAEs tend to peak near substorm onset. We argue that the different LAE behavior results from different pitch‐angle distributions (PADs) of the ion source population. Ion PADs are isotropic during substorm recovery phase for the 11 October 2008 event and have empty loss cone for the 5 April 2010 event. For both cases, LAE intensification marks the onset of activity in the magnetotail and precedes the large substorm onset. We conclude that the LAE production starts in the transition region between the magnetotail and ring current and may expand/move into the inner magnetosphere together with ring current formation. Key Points: Dynamics of low‐altitude (LAE) energetic neutral atom emissions in substorms The different LAE behavior results from different ion pitch‐angle distributions LAEs intensification precedes the large substorm onset